Efficient seismic response data storage and transmission using ARX model-based sensor data compression algorithm. - Yunfeng Zhang
This paper presents a linear predictor (LP)-based lossless sensor data compression algorithm for efficient transmission, storage and retrieval of seismic data. Auto-Regressive with eXogenous input (ARX) model is selected as the model structure of LP. Since earthquake ground motion is typically measured at the base of monitored structures, the ARX model parameters are calculated in a system identification framework using sensor network data and measured input signals. In this way, sensor data compression takes advantage of structural system information to maximize the sensor data compression performance. Numerical simulation results show that several factors including LP order, measurement noise, input and limited sensor number affect the performance of the proposed lossless sensor data compression algorithm concerned. Generally, the lossless data compression algorithm is capable of reducing the size of raw sensor data while causing no information loss in the sensor data.
Keywords: Data compression; Instrumentation; Seismic response; Sensor network; System identification